Quality of Drug Side Effect Information as Foundation for Pharmacy Reputation and Buyer Confidence - Darmawan, Didit; Ramadhani, Diana (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the role of pharmacists' quality in explaining drug side effects in building pharmacy brand reputation and shaping buyers' confidence to reuse the same service. The research employs a qualitative literature study with a content analysis approach, drawing upon various relevant scholarly sources. The findings indicate that explanations of side effects delivered patiently, clearly, and using language comprehensible to patients create feelings of safety and value. These impressions leave a lasting impact that is subsequently shared with others, organically building brand reputation. Each satisfactory interaction regarding side effect explanations reinforces patients' conviction that the pharmacy is the appropriate destination for future visits. This confidence evolves into loyalty that withstands the allure of lower prices or promotions from competing pharmacies. Pharmacists' professionalism in communicating medication risks yields a dual benefit: protecting patients from medical harm while simultaneously safeguarding the pharmacy business from competition. The practical implications of this study underscore the necessity of prioritizing communication training for pharmacists, developing consistent operational standards, and recognizing that every patient interaction constitutes a long-term investment in brand reputation.